Mitochondrial Dysfunction in the Pathogenesis of Rett Syndrome: Implications for Mitochondria-Targeted Therapies - Shulyakova, Natalya; Andreazza, Ana C.; Mills, Linda R.; Eubanks, James H. (Frontiers in Cellular Neuroscience, 2017)
First described over 50 years ago, Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by mutations of the X-linked MECP2 gene. RTT affects predominantly females, and has a prevalence of roughly 1 in every 10,000 female births. Prior to the discovery that mutations of MECP2 are the leading cause of RTT, there were suggestions that RTT could be a mitochondrial disease. In fact, several reports documented altered mitochondrial structure, and deficiencies in mitochondrial enzyme activity in different cells or tissues derived from RTT patients. With the identification of MECP2 as the causal gene, interest largely shifted towards defining the normal function of MeCP2 in the brain, and how its absence affects the neurodevelopment and neurophysiology. Recently, though, interest in studying mitochondrial function in RTT has been reignited, at least in part due to observations suggesting systemic oxidative stress does play a contributing role in RTT pathogenesis. Here we review data relating to mitochondrial alterations at the structural and functional levels in RTT patients and model systems, and present a hypothesis for how the absence of MeCP2 could lead to altered mitochondrial function and elevated levels of cellular oxidative stress. Finally, we discuss the prospects for treating RTT using interventions that target specific aspects of mitochondrial dysfunction and/or oxidative stress.